PROFIL SISWA YANG MEMPUNYAI KEPERCAYAAN DIRI RENDAH DI SMA NEGERI 4 CIMAHI - Leni Marlina; Siti Fatimah; Riesa Rismawati Siddik (IKIP Siliwangi, 2022)
This research aims to be able to find out the confidence profile of class XI Ipa students, so that it can be known the number of students who have confidence in high, medium, and low categories. Self-confidence is a keyaninan or self-assessment of all that concerns ability, excess after deficiency. Confidence will continue to grow if trained and accustomed. The methods used in this study use qualitative approaches and descriptive methods. The sample in this study was taken in students of class XI Ipa at State High School 4 Cimahi, taking a sample of 35 students, including 11 men and 24 women. Data collection techniques in the form of spreading confidence questionnaires to students. So based on the results of the spread of this questionnaire can be concluded there are 20 students (57%) who are categorized as having high self-confidence, 10 students (29%) categorized as having moderate self-confidence, and 5 students (14%) who are categorized as having low self-confidence.Keywords: Student Profile, Confidence